8x-3=9-2x
![8x - 3 = 9 - 2x 8x - 3 = 9 - 2x](https://tex.z-dn.net/?f=8x+-++3+%3D+9+-+2x)
Answers
Answered by
24
8x-3 = 9-2x
=> 8x+2x = 9+3
=> 10x = 12
=> x = 12/10
=> x = 1.2
hope this helps u..
=> 8x+2x = 9+3
=> 10x = 12
=> x = 12/10
=> x = 1.2
hope this helps u..
Answered by
6
8x+2x=9+3
10x=12
x=1.2
10x=12
x=1.2
Similar questions
Computer Science,
9 months ago
World Languages,
9 months ago
Social Sciences,
9 months ago
Math,
1 year ago
Physics,
1 year ago
English,
1 year ago
English,
1 year ago